Synthesis and structural characterization of twin liquid crystalline perylenebisimides - Prajitha, K. P.; Asha, S. K. (New Journal of Chemistry, 2016)
A series of twin perylenebisimide (PBI) molecules were synthesized and characterized having the structure PBI-(methylene spacer)-n-PBI where the length of the central polymethylene spacer segment was varied from n = 1 to 12. The PBI unit was imidized with an ethyl hexyl branched alkyl segment at the terminal and pentadecyl phenol at the other end which was linked through the polymethylene spacer to form the twin molecules. The differential packing afforded by the odd and even spacer central methylene segments resulted in an odd-even oscillation of the melting transitions as well as their enthalpies with higher values observed for the even twins. The odd-even oscillation was quite prominent for the spacers up to n < 7 after which it tapered off. PBI-T1 and PBI-T3 exhibited tendencies to form smectic liquid crystalline (LC) phases while most of the higher membered twin molecules exhibited tendencies for high temperature nematic phases. The ability to control the crystalline or mesogenic nature of the PBI molecules, which constitute an important member of the n type rylenebisimide family that finds application as electron transporters in field effect transistors (FETs) and organic solar cells, is promising as it provides a handle to design systems whose bulk packing is pre-defined to suit the requirements of the application.